Stability trends of Jinpingzi landslide: A numerical study - Xu, Bo; Huang, Qisong; Qian, Yuandi (Frontiers in Earth Science, 2022)
The occurrence and development of creeping landslides lead to a gradual destruction of the affected environment; therefore, research into creeping landslide stability trends based on the monitoring of landslide data is of considerable practical value. We investigated the Jinpingzi landslide area II using strength subtraction to analyze the relationship between stress and strain at important points and the stability of the landslide. The results confirm the relationship between the internal failure pattern, safety factor, and key point displacement of creeping landslides. Furthermore, the results confirm the change rules of displacement, in addition to changes in the safety factor. By combining the surface displacement monitoring data of Jinpingzi landslide area II, its stability trend was analyzed based on the established relationship model between deformation displacement and internal failure characteristics of creeping landslides. The results demonstrate that the Jinpingzi landslide area II is in a stable damage deformation. The sliding surface formed in the landslide and the results obtained using the model of the Jinpingzi landslide area II are consistent with the actual situation determined by analysis in the field and exploring the geology.